The emergence of the Hebrew Christian movement in nineteenth-century Britain - Darby, Michael R. (Studies in the history of religions, 2010)
In nineteenth-century Britain, the majority of the Jewish people were involved in a process of assimilation or acculturation and most of those who embraced Christianity were content to worship in a Gentile milieu despite being enjoined by the Old and New Testament scriptures to maintain their national distinctiveness and consequently their leadership position in the Christian Church. A few debated the implications of incorporating into their worship the observance of Jewish tradition, and advocated the theological and liturgical independence of Hebrew Christianity, characterized by opponents as the "scandal of particularity." Members of the Jewish community regarded these believers as apostates and Gentile Christians viewed them ambivalently as historically and eschatologically influential, but of no particular contemporary significance in Britain. Jewish, and Gentile Christian writers for the most part view Hebrew Christianity as a marginal movement, while Jewish Christian historians regard the movement as central to salvation history. Previous scholarship has documented several Hebrew Christian initiatives, but this monograph breaks new ground by identifying almost forty discrete institutions as components of a century-long movement. The book analyses the major pioneers, institutions and ideologies of this movement and recounts how, through identity negotiation, Hebrew Christians - and also their gentile supporters - prepared the way for the development in the twentieth century of Messianic Judaism